Ksiądz Styczeń czyta Norwida. Vade-mecum jako lektura- -inspiracja - FERT, Józef F. (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
In the essay, the author has included a textological analysis of the numerous notes Fr. Prof. Tadeusz Styczeń, the late editor-in-chief of Ethos, made in his copy of Cyprian Norwid’s Vade-mecum throughout the years of his repeated reading of that volume. The notes in question became subsequently the basis for the ideas Styczeń put forward and developed in his articles on moral philosophy. Styczeń frequently referred to Norwid, whom he believed to have been the best Polish philosopher poet. Summarized by Dorota Chabrajska